The economics of time and ignorance - O'Driscoll, Gerald P. (Foundations of the market economy series., 1996)
The Economics of Time and Ignorance is one of the key works in the development of modern Austrian economics. Building on the work of Hayek, Lachmann and Shackle, its authors developed a powerful critique of neo-classical economics, in particular of its over deterministic models and its pretence of knowledge. The work is reprinted here in full and is supplemented by a substantial new introduction which outlines the major developments in the area since the book's original publication a decade ago.